2022
DOI: 10.3892/etm.2022.11268
|View full text |Cite
|
Sign up to set email alerts
|

Favorable outcomes of patients with sickle cell disease hospitalized due to COVID‑19: A report of three cases

Abstract: Sickle cell disease (SCD) is one of the most frequent and severe monogenic disorders, affecting millions of individuals worldwide. SCD represents a fatal hematological illness, characterized by veno-occlusive events and hemolytic anemia. Hemolytic anemia is caused by abnormal sickle-shaped erythrocytes, which induce parenchymal destruction and persistent organ damage, resulting in considerable morbidity and mortality. During the coronavirus disease 2019 (COVID-19) pandemic, patients with SCD were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…These manifestations have been reported since the beginning of the pandemic with significant frequency, although the cause-effect correlation cannot always be clearly determined. There are points of disagreement about the biological impact of COVID-19 in individuals with sickle cell disease, but most authors seem to agree that SARS-CoV-2 can act as a trigger for vaso-occlusive crises and acute chest syndrome ( 14 , 29 , 30 , 32 , 34 , 37 , 39 , 42 , 43 , 45 , 46 , 67 , 71 , 72 , 74 , 75 , 77 , 79 , 82 , 84 , 86 , 90 , 92 , 98 , 104 , 106 , 109 , 112 , 118 ). Explanations for this are grounded in empirical data and well-established knowledge about the mechanisms by which infections trigger complications of sickle cell disease.…”
Section: Discussionmentioning
confidence: 99%
“…These manifestations have been reported since the beginning of the pandemic with significant frequency, although the cause-effect correlation cannot always be clearly determined. There are points of disagreement about the biological impact of COVID-19 in individuals with sickle cell disease, but most authors seem to agree that SARS-CoV-2 can act as a trigger for vaso-occlusive crises and acute chest syndrome ( 14 , 29 , 30 , 32 , 34 , 37 , 39 , 42 , 43 , 45 , 46 , 67 , 71 , 72 , 74 , 75 , 77 , 79 , 82 , 84 , 86 , 90 , 92 , 98 , 104 , 106 , 109 , 112 , 118 ). Explanations for this are grounded in empirical data and well-established knowledge about the mechanisms by which infections trigger complications of sickle cell disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is conflicting empirical evidence on whether patients with SCD experience more severe COVID-19 disease, and whether their mortality rate is greater than the general population. Some published case series and observational cohort studies reported a relatively mild and uncomplicated course [ [17] , [18] , [19] , [20] ] while others reported an increased risk of complications, hospitalization and/or death [ [21] , [22] , [23] , [24] , [25] , [26] ]. A systematic review of case reports and observational cohort studies of patients with SCD and COVID-19 described that adults typically had a mild to moderate course, with few respiratory symptoms, similar to patients without SCD; studies that described more severe disease in patients with SCD and COVID-19 reported prolonged hospitalization with hypoxia, pneumonia, prolonged fever, multisystem inflammation, as well as complications typical in SCD, such as acute chest syndrome and severe pain crisis [ [26] , [27] , [28] , [29] ].…”
Section: Overview Of Covid-19 Risk and Vaccination Benefits In Common...mentioning
confidence: 99%
“…Patients with SCD at times require blood transfusions, and this may interfere with their cardiovascular health if they are also infected with COVID-19. Blood coagulation and endothelial damage are observed in patients infected with COVID 19; therefore, patients with SCD may have a higher risk as they already exhibit a poor immune system, and their blood cells are prone to sickling as well as related cardiovascular problems (20).…”
Section: Introductionmentioning
confidence: 99%